Infiltrado inflamatório em glândulas salivares e amostras hepáticas de pacientes com hepatite C crônica: padrão de distribuição e imunofenótipo - Patrícia Carlos Caldeira (2014)
Chronic hepatitis C affects over 3% of global population and has become the major cause of cirrhos is and hepatic transplantation in Occidental world. It is caused by the hepatitis C virus and hepatic inflammation is one of the consequences of the infection. Among extra-hepatic alterations related to salivary glands, sicca syndrome affects between 4 and 57% of patients. Nevertheless, few studies intended to elucidate the composition of the inflammatory infiltrate and its possible relation to other features of the disease. The present study aimed to characterize the composition and distribution of the inflammatory infiltrate seen in minor salivary glands of patients with chronic hepatitis C, comparing with liver inflammation and laboratorial data of patients. Immunohistochemistry was performed to CD3 (T lymphocytes), CD20 (Blymphocytes), CD8 (cytotoxic T lymphocytes), CD4 (helperT lymphocytes), CD57 (natural killer cells), CD68 (macrophages),andS100 (dendritic cells) in 61 samples of salivary glands and 59 of liver. Results were expressed in percentage of positive cells. The pattern of distribution of the inflammatory infiltrate was classified as focal or diffuse. Kruskal-Wallis, Mann-Whitney, ANOVA e t de Student statistical tests were used and p values lower than 0.05 were considered statistically significant. Diffuse inflammatory infiltrate was present in 57.4% of salivary glands and in 13.6% of liver biopsies. CD3+and CD20+were the most frequent cells in both tissues, with a CD3/CD20 ratio of 1.17 in salivary glands and 1.90 in liver. CD4+/CD8+ratio in salivary glands was 0.30 and 1.06 in liver. CD57+, CD68+, and S100+were found in a low percentage in both tissues. Higher CD3+, CD20+, and CD8+indexes (p<0.05) were seen in SG with focal infiltrate than with diffuse infiltrate. Comparisons of all markers in salivary glands and METAVIR grade (A0, A1 or A2), viral genotype (1a, 1b or3a), viral load (low or high), and presence of HCV RNA in salivary gland (present or absent) were not statistically significant (p>0.05). Comparison between all salivary glands and liver indexes revealed statistically significant differences (p<0.05), with higher indexes found in liver, except S100+.We concluded that T and B lymphocytes were the most common leucocytes found in salivary glands of patients with chronic hepatitis C, especially cytotoxic T cells. The percentage of leucocyte subtypes detected in salivary glands is related to the distribution pattern of inflammation, but not to METAVIR grade, viral genotype, viral load, and local presence of HCV RNA. The same inflammatory cells found in liver can be seen in salivary glands, except CD4+,whichwere scarce in this tissue, but liver reveals a higher proportion of cells.